Determinants of Insurance Financial Mobilization and Public Budget Support in Iraq - Mohammad Ghazi Nussaif; Muayad Hameed Majdi; Zainab Sadeq Ibrahim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Insurance companies mobilize financial resources through premiums, investments, and reinsurance agreements, contributing to economic stability via tax revenues and employment generation. Specific Background: The Iraqi General Insurance Company and National Insurance Company channel profits to support public finances, yet their fiscal contribution mechanisms remain underexamined. Knowledge Gap: Empirical evidence quantifying determinants of financial resource mobilization in Iraqi insurance companies and their impact on state budget support is limited. Aims: This research identifies factors influencing mobilized financial resources and examines their contribution to the state budget during 2009-2022. Results: Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study reveals total profits do not significantly affect public treasury shares, with both companies contributing under one percent of total public revenues. Novelty: This investigation provides the first systematic empirical assessment of resource mobilization determinants in Iraqi government insurance companies using variance-based structural equation modeling. Implications: Current regulatory frameworks fail to optimize insurance sector contributions to fiscal sustainability, necessitating policy reforms including tax incentives and enhanced institutional capacity.Keywords : Insurance Financial Resources, State Budget Support, Iraqi Insurance Sector, PLS-SEM Analysis, Economic Growth ContributionHighlight : Insurance company profits show no statistically significant impact on public treasury contributions. Iraqi insurance sector contributes less than 1% of total government revenues. Inflation rate strongly correlates with public treasury share at 89.5% coefficient.